Trigone ventricular glioblastoma multiforme with trapped temporal horn: A case report - Liu, Lei; Wang, Shaozhen; Dong, Xuetao; Liu, Yaodong; Wei, Liudong; Kong, Linghong; Zhang, Qingjun; Zhang, Kun (Frontiers in Oncology, 2022)
Background: Intraventricular glioblastoma multiforme (GBM) is extremely rare, especially in the trigone region. This report presents a case of trigone ventricular GBM with trapped temporal horn (TTH). Case Presentation: A 59-year-old woman was admitted to our department with a 1-month history of rapidly progressive headache, nausea, and weakness in the right lower extremity. Head non-contrast computed tomography and enhanced magnetic resonance imaging (MRI) revealed a trigone ventricular mass lesion with TTH and heterogeneous enhancement. The lesion was found 18 months ago as a small asymptomatic tumor mimicking ependymoma. This neoplasm was removed subtotally through the right parieto-occipital approach guided by neuroendoscopy. A ventriculoperitoneal shunt was subsequently performed to relieve TTH. The final pathological diagnosis was GBM. Unfortunately, 36 days after the first surgery, the patient died due to her family’s decision to refuse therapy. Conclusion: This rare case shows that GBM should be considered in the differential diagnosis of trigonal tumors. In this case, the tumor possibly originated from the neural stem cells in the subventricular zone. Patients with intraventricular GBM have a worse prognosis, and careful follow-up and early surgery for small intraventricular tumors are necessary, even for those with ependymoma-like radiological findings.